Analisis Pemberian Restitusi kepada Keluarga Korban Kekerasan Fisik yang Menyebabkan Kematian Sebagai Bentuk Keadilan Hukum - Anisa Puspitasari; Rasji Rasji (Dinasti Research, 2024)
Physical violence refers to any act of aggression directed at another individual by a person using their own body that results in harm or even death to the target of the aggression. The Cibadak District Court Decision Number 85/Pid.B/2022, which explains that Jana Sahroni committed an act of physical violence that resulted in the victim's death, is the focus of this legal research. The judge sentenced Sahroni to seven (seven) years in prison without imposing any restitution to be given to the victim's family, who was left behind. the extent of the perpetrator's legal liability for using physical force that results in death and if the victim's family can receive compensation. This legal writing, which is normative juridical research, focuses on comprehending laws and regulations and evaluating the legal sources that were employed through a literature review. As a result, a decision will eventually be made about the legalisation of violent crimes that result in death as well as the payment of compensation to the victim's family.